2022
DOI: 10.7819/rbgn.v24i2.4172
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Innovation Capabilities and their Impact on Export Performance in Times of Economic Crisis

Abstract: Purpose -To determine the mediator role of innovative dynamic capabilities in performance in the internationalisation strategy of firms during periods of economic crisis.Theoretical framework -We base our study on the Theory of Dynamic Capabilities, as a response to the environment produced by an economic crisis. Two firm models are analysed in accordance with their internationalisation strategy: born-global and gradual internationalisation firms.Design/methodology/approach -We propose two hypotheses which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The findings of this study are consistent with Bhat and Momaya (2020) who revealed that employing INVC significantly determines the EXPERF of emerging market multinationals in the context of the Indian pharmaceutical industry. Also, Ledesma-Chaves and Gaitán (2022) concluded that INVCs are essential for entering new markets and they lead to EXPERF improvements in Spanish exporting firms. Similarly, Castillo et al.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings of this study are consistent with Bhat and Momaya (2020) who revealed that employing INVC significantly determines the EXPERF of emerging market multinationals in the context of the Indian pharmaceutical industry. Also, Ledesma-Chaves and Gaitán (2022) concluded that INVCs are essential for entering new markets and they lead to EXPERF improvements in Spanish exporting firms. Similarly, Castillo et al.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The extant literature emphasizes that innovation is a key driver for firms' ability to survive in dynamic and intensely competitive environments (Bagheri et al, 2019;Castillo et al, 2022) and it creates firm-specific advantages (Oura et al, 2016). Despite the fact that a stream of literature recognizes the importance of innovation capabilities in enhancing export performance (Ledesma-Chaves and Gait an, 2022;Ortigueira-S anchez et al, 2022;Ribau et al, 2017), findings on this relationship are not conclusive (Bıçakcıo glu et al, 2020;Castillo et al, 2022). Also, empirical based-evidence on the relationship in developing economies is scarce (Ortigueira-S anchez et al, 2022).…”
Section: Innovation Capabilities and Export Performancementioning
confidence: 99%
See 2 more Smart Citations
“…These consider export performance (Nguyen et al. , 2022; Pyper et al ., 2022; Jeong and Chung, 2022), Dynamic capabilities (Ledesma-Chaves and Arenas-Gaitán, 2022; Umrani et al ., 2022; Falahat et al ., 2021), Institutionalism (Malca et al ., 2022; Griffith and Yalcinkaya, 2022).…”
Section: Introductionmentioning
confidence: 99%